Should phosphate management be limited to the KDIGO/ KDOQI guidelines?. Issue 4 (19th April 2018) - Dhillon‐Jhattu, Sangeet; Sprague, Stuart M.
Abstract: Hyperphosphatemia is a common complication of CKD. Prior to development of overt hyperphosphatemia, there are several adaptive mechanisms that occur to maintain normal phosphorus equilibrium in patients with CKD. These include an early and progressive rise in fibroblast growth factor 23 (FGF 23), followed by an increase in parathyroid hormone (PTH) with a decrease in 1, 25‐dihydroxyvitamin D (1, 25 Vit D). Over the last 20 years, a large number of studies have shown that hyperphosphatemia is a strong predictor of adverse clinical outcomes including increased incidence of vascular calcification, cardiovascular disease, and all‐cause mortality in both individuals with CKD as well as those with normal kidney function. In addition, elevations of both FGF 23 and PTH are independently associated with increased morbidity and mortality. Therefore, phosphorus lowering therapies are a vital part of the treatment strategy for patients with CKD and include dietary phosphorus restriction, treatment with phosphate binders and removal with dialysis. However, there has been a lack of high quality evidence demonstrating beneficial effects of phosphate lowering therapy on clinical outcomes. Furthermore, we do not have definitive data as to whether effective phosphate control with phosphate binders will prevent elevations in FGF 23, and whether lowering FGF 23 levels will lead to improved patient outcomes. As a result of the presently available data (or lack thereof) clinical guidelines recommend treatment only after hyperphosphatemia develops and in dialysis patients; KDOQI recommends a treatment target of less than 5.5 mg/dL, whereas KDIGO recommends treating "towards normal." We are left with a clinical dilemma, being whether these recommendations are adequate, or should we be more aggressive in phosphate management. In this article, our goal is to discuss some of the studies concerning the adverse consequences of phosphate excess and as well as elevated FGF 23 levels, and present our opinion on what we believe the goal of treatment should be.